Evaluation of the Achievement Development Program at the Taekwondo Sports Education and Training Center for Students in Central Java Province - David Hasian Barutu Sinaga; Nasuka Nasuka; Ipang Setiawan (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2022)
The purpose of this study is to systematically evaluation in the PPLOP coaching Program, the CIPP model (Context, Input, Process, Product) in taekwondo PPLOP Central Java can be implemented and can be evaluated to stimulate institutional efforts in the long term to be able to take steps towards coaching program in the future. The evaluation model research uses the CIPP model with a mix methods approach. The samples in this study were 4 PPLOP hall administrators, 4 coaches and 12 athletes in the taekwondo PPLOP central java. The results of the evaluation of the achievement development program at the taekwondo sports training center for students in Central Java Province based on the management of the Central Java PPLOP hall administrators, trainer and athletes for taekwondo PPLOP Central Java are mostly in good category. Process evaluation based on central java PPLOP hall management, trainers, and Central Java PPLOP taekwondo athletes are in good category. Product evaluation based on central java PPLOP hall managemet, Central java PPLOP taekwondo trainers and athletes are in the adequate category.